2022
DOI: 10.1080/15592324.2022.2114647
|View full text |Cite
|
Sign up to set email alerts
|

Strigol induces germination of the facultative parasitic plant Phtheirospermum japonicum in the absence of nitrate ions

Abstract: Root parasitic plants in the family Orobanchaceae, such as Striga and Orobanche spp., infest major crops worldwide, leading to a multibillion-dollar loss annually. Host-derived strigolactones (SLs), recognized by a group of α/β hydrolase receptors (KAI2d) in these parasites, are important determinants for germinating root parasitic plants near the roots of host plants. Phtheirospermum japonicum , a facultative hemiparasitic Orobanchaceae plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Plant roots and AMF respond to each other in the course of symbiosis (Dhanker et al, 2020;Nasir et al, 2021), and the roots and AMF are capable of mutual tropism growth. We analyzed the host tropism of AMF (Sbrana and Giovannetti, 2005;Pineda-Martos et al, 2021;Ogawa and Shirasu, 2022a;Ogawa et al, 2022b), and our preliminary results suggest that the host tropism of spores was significantly inhibited by myristate application. The main purpose of this study was to explore the mycorrhizal colonization of AMF, so the hairy roots and spores were not cultured in separate compartments, and we only observed and analyzed the phenomenon of the host tropism in AMF preliminarily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant roots and AMF respond to each other in the course of symbiosis (Dhanker et al, 2020;Nasir et al, 2021), and the roots and AMF are capable of mutual tropism growth. We analyzed the host tropism of AMF (Sbrana and Giovannetti, 2005;Pineda-Martos et al, 2021;Ogawa and Shirasu, 2022a;Ogawa et al, 2022b), and our preliminary results suggest that the host tropism of spores was significantly inhibited by myristate application. The main purpose of this study was to explore the mycorrhizal colonization of AMF, so the hairy roots and spores were not cultured in separate compartments, and we only observed and analyzed the phenomenon of the host tropism in AMF preliminarily.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that the hairy roots and AMF have the ability to grow toward each other, and called the ability of AMF to grow toward host plant roots as host tropism (Ogawa and Shirasu, 2022a;Sbrana and Giovannetti, 2005;Pineda-Martos et al, 2021;Ogawa et al, 2022b). In addition, some roots grew toward AMF, and the germ tube could contact the roots after spore germination immediately.…”
Section: Sand Culture System (Experiments 2)mentioning
confidence: 96%